Test of Lead (Pb) and Zinc (Zn) on Tiger Shrimp (Penaeus monodon) at Kalanganyar Market, Sidoarjo with Atomic Absorption Spectrophotometer (AAS) : Uji Kadar Timbal (Pb) dan Seng (Zn) pada Udang Windu (Penaeus monodon) di Sidoarjo Dengan Metode Atomic Absorption Spectrophotometer (AAS) - Sejati, Risqi Agil Wahyu; Hanum, Galuh Ratmana; Pramushinta, Intan Ayu Kusuma (Medicra (Journal of Medical Laboratory Science/Technology), 2022)
Sidoarjo City in East Java Province has a pond area of up to 7.68%. One of the cultivations developed in ponds is tiger shrimp (Penaeus monodon), which are mostly sold in Sidoarjo. The presence of metals in aquatic bodies comes from natural sources that enter can be the erosion of mineral rocks found in the aquatic environment. Tiger shrimp is one type of shrimp that is preferred by most Indonesian people. If this shrimp is contaminated by heavy metals, it will harm the people who consume it. This research was conducted to find out the levels of heavy metals Timbal (Pb) and Seng (Zn) contained in tiger shrimp (Penaeus monodon) windu shrimp in the market of Sidoarjo with the Atomic Absorption Spectrophotometer (AAS) method. This research was conducted at the Laboratory of Applied Chemical Technology Medical Laboratory of the Faculty of Health Sciences, University of Muhammadiyah Sidoarjo and the Chemistry Laboratory of FMIPA of Maulana Malik Ibrahim University of Malang. Data analysis methods use measurement and observation as well as descriptive statistical analysis. The results of heavy metal levels in this study obtained the highest levels of lead heavy metals (Pb) of 0.596 mg/kg while the lowest levels amounted to 0.544 mg/kg and the highest levels of zinc heavy metals (Zn) amounted to 3.930 mg/kg while the lowest levels amounted to 3.016 mg/kg.